Studies on Length-weight and Length-length Relationships, Relative Condition Factor and Fulton’s Condition Factor of Hemiculter leucisculus (Pisces: Cyprinidae) from the Southwestern Caspian Sea Basin - Mousavi-Sabet, H.; Habibi, A.; Bagherpur, O. (Our Nature, 2013)
In this study, length-weight (LWR) and length-length relationships (LLRs), relative condition factor (krel) and Fulton’s condition factor (k) of 235 Hemiculter leucisculus Basilewsky were determined between the periods of March 2012 to February 2013 in Sefidroud River, in the Southwestern Caspian Sea basin. The maximum recorded total length for males and females were 16.90 cm and 18.10 cm, respectively. The length-length relationships among the total length (TL), fork length (FL) and standard length (SL) for H. leucisculus were found to be highly significant (r2>0.968, p<0.001). The length-weight relationship shows the obtained b values for males, females and male-females were 2.549, 2.680 and 2.465 respectively, which indicated a negative allometric growth trend of this species. Also, relative condition factor (Krel) for males, females and male-females were 0.710, 0.622 and 0.743 respectively and Fulton’s condition factor (K) for males, females and male-females were 0.922, 0.842 and 0.843 respectively. These results will be useful for ?shery managers to impose adequate regulations for sustainable ?shery management. DOI: http://dx.doi.org/10.3126/on.v11i1.8240 Our Nature Vol.11(1) 2013: 25-30